PENGARUH PENDAPATAN DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PKL DI JALAN GADING FAJAR PADA MASA PANDEMI COVID-19 - Laily Muzdalifah (Universitas Nahdlatul Ulama Sidoarjo, 2020)
The purpose of this study was to determine the effect of income and consumer motivation on purchasing decisions on Street Vendors (PKL) on Jalan Gading Fajar Sidoarjo during the Covid-19 pandemic. This influence test is carried out to find out the effect partially and simultaneously. Quantitative research is the type of research used in this study. The research sample of 100 respondents. The primary data source is the result of filling out a questionnaire given to consumers who buy at PKL Jalan Gading Fajar. Data analysis technique is done by testing the hypothesis that is by doing a t test (partial) but also an F test (simultaneous). The results of the study are known that the income variable has a significant effect on purchasing decisions. For consumer motivation variables have a significant influence on purchasing decisions. For simultaneous testing it is known that consumer income and motivation significantly influence purchasing decisions.